Comprehensive protocols for culturing and molecular biological analysis of IBD patient-derived colon epithelial organoids - Gopalakrishnan, Shreya; Bakke, Ingunn; Hansen, Marianne Doré; Skovdahl, Helene Kolstad; Granlund, Atle van Beelen; Sandvik, Arne K.; Bruland, Torunn (Frontiers in Immunology, 2023)
There are many unanswered questions regarding responses to proinflammatory signals in intestinal epithelial cells (IECs). For example, chemokines secreted by IECs upon external stimuli play multifunctional roles in both homeostasis and during inflammation. Several chemokines are upregulated during active inflammatory bowel disease (IBD), which is associated with an increased influx of immune cells into the gut mucosa. Therefore, studies on how chemokines are regulated in the intestinal epithelium may identify putative treatment targets in IBD. More recently, patient-derived ex vivo models such as intestinal organoids have facilitated molecular analysis of epithelial alterations in IBD patients own cells. Here, we describe refined experimental protocols and methods for the generation and maintenance of IBD patient-derived colonic organoids (colonoids) culture. We also give detailed description of medium, and supplements needed for colonoid establishment, growth, and differentiation, including production of Wnt-3A and Rspondin1 enriched media. Further, we present protocols for RNA and protein isolation from human colonoids, and subsequent gene expression analysis and Western blotting for e.g., signal transduction studies. We also describe how to process colonoids for chemokine protein expression analysis such as immunostaining, confocal imaging, and detection of secreted chemokines by e.g., enzyme-linked immunosorbent assay (ELISA). As proof of principle, we give examples of how the chemoattractant CCL20 can be regulated and expressed in colonoids derived from IBD-patients and healthy controls upon ligands-driven inflammation.